Investigating the core microbiota and its influencing factors in traditional Chinese pickles. (September 2021) - An, Feiyu; Sun, Huijun; Wu, Junrui; Zhao, Chunyan; Li, Tong; Huang, Heting; Fang, Qiang; Mu, Endong; Wu, Rina
Graphical abstract: Highlights: It reveals the microbial community structure of various traditional Chinese pickles. Weissella, Lactobacillus and yeast were the core strains in various types of pickles. Major ingredients and manufacturing process can affect the microflora in pickles. The core microorganisms may adapt to the changing internal fermentation environment. Abstract: Pickles are a type of traditional fermented food in Northeast China that exhibit a broad variety of preparations, flavors and microbial components. Despite their widespread consumption, the core microorganisms in various traditional pickles and the precise impact of ecological variables on the microbiota remains obscure. The present study aims to unravel the microbial diversity in different pickle types collected from household (12 samples) and industrial (10 samples) sources. Among these 22 samples tested, differences were observed in total acid, amino acid nitrogen, nitrite, and salt content. Firmicutes and Ascomycota emerged as the predominant microbial phyla as observed by Illumina MiSeq sequencing. Amongst these, the commonly encountered microorganisms were Lactobacillus, Weissella and yeast. Comparative analysis based on non-metric multidimensional scaling (NMDS), showed that the microbial community in the pickles was affected by external conditions such as major ingredients and manufacturing process. Correlation analysis further showed that the resident core microorganisms in pickles could adapt to the changing internal fermentation environment. The insights gained from this study further our understanding of traditional fermented foods and can be used to guide the isolation of excellent fermented strains.